The implications and prospect of cuproptosis-related genes and copper transporters in cancer progression - Zhao, Qianwen; Qi, Tonggang (Frontiers in Oncology, 2023)
Currently, Cancer has become one of the major public health problems worldwide. Apoptosis is an important anti-cancer defense mechanism, which is used in the development of targeted drugs. Because cancer cells have endogenous resistance to apoptosis,the clinical efficacy of related drugs is not ideal. Therefore, non-apoptotic regulatory cell death may bring new therapeutic strategies for cancer treatment. Cuproptosis is a novel form of regulatory cell death which is copper-dependent, regulated and distinct from other known cell death regulatory mechanisms. FDX1,LIAS,and DLAT named cuproptosis-related genes play an essential role in regulating cuproptosis. Meanwhile, abnormal accumulation of copper can be observed in various malignant tumors. The correlation has been established between elevated copper levels in serum and tissues and the progression of several cancers. Copper transporters, CTR1 and Copper-transporting ATPases(ATP7A and ATP7B), are mainly involved in regulating the dynamic balance of copper concentration to maintain copper homeostasis. Thus,cuproptosis-related genes and copper transporters will be the focus of cancer research in future. This review elaborated the basic functions of cuproptosis-related genes and copper transporters by retrievalling PubMed. And then we analyzed their potential relationship with cancer aiming to provide theoretical support and reference in cancer progression, diagnosis and treatment for future study.